Metabolic Variation Dictates Cardiac Pathogenesis in Patients With Tetralogy of Fallot - Liu, Jianyang; Kong, Shuxin; Song, Shubo; Dong, Haoju; Zhang, Zhidong; Fan, Taibing (Frontiers in Pediatrics, 2022)
Background: Herein we aimed to analyze cardiac metabolic reprogramming in patients with tetralogy of fallot (ToF). Methods: Cardiac metabolic reprogramming was analyzed through comprehensive bioinformatics analysis, which included gene set enrichment, gene set variation, and consensus clustering analyses, so as to assess changes in metabolic pathways. In addition, full-spectrum metabolomics analysis was performed using right atrial biopsy samples obtained from patients with ToF and atrial septal defect (ASD) before cardiopulmonary bypass; ultrahigh performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) was used to construct a metabolic map of cardiac metabolic reprogramming in cyanotic congenital heart disease. Results: The metabolic maps of carbohydrate metabolic process and heme metabolism were significantly activated, while bile acid metabolism, lipid droplet, and lipid binding were primarily restrained in ToF samples as compared to that in ASD samples. The reprogramming of butanoate metabolism was identified basing on the UPLC–MS/MS detection and analysis in myocardial hypoxia damage in cyanotic heart disease. Finally, the butanoate metabolism-related hub regulators ALDH5A1 and EHHADH were identified and they were significantly downregulated in ToF samples. Conclusions: The metabolic network of butanoate metabolism,involved in ALDH5A1 and EHHADH, which could contribute to myocardial tissue damage in cyanotic congenital heart of ToF. Our results provide further insights into the mechanisms underlying metabolic reprogramming in cyanotic congenital heart disease, and could lead to the identification of potential therapeutic targets.